2018
DOI: 10.1155/2018/6546808
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Citrus Lemon Reduces Liver Injury Induced by Carbon Tetrachloride in Rats

Abstract: Fermented lemon juice displays a variety of important biological activities, including anti-inflammatory and antioxidant capabilities. The aim of the present study is to investigate hepatic-protective effects of no-sugar-added fermented lemon juice (FLJ) for liver inflammation caused by carbon tetrachloride (CCl4) in rats. Rats are divided into six groups: H2O, CCl4 + H2O, CCl4 + silymarin, and CCl4 plus three different FLJ doses by oral administration, respectively. The results show that the contents of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…CCl 4 -induced hepatic damage was further confirmed by histopathological examination which showed degenerative changes and massive necrosis. Our results are consistent with those of Chen et al 35 and Abdelhafez et al 38,39 Biological systems aim to protect themselves against oxidative injury with several antioxidants which include free radical scavenging molecules, e.g. GSH, and antioxidant enzymes, e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CCl 4 -induced hepatic damage was further confirmed by histopathological examination which showed degenerative changes and massive necrosis. Our results are consistent with those of Chen et al 35 and Abdelhafez et al 38,39 Biological systems aim to protect themselves against oxidative injury with several antioxidants which include free radical scavenging molecules, e.g. GSH, and antioxidant enzymes, e.g.…”
Section: Discussionsupporting
confidence: 93%
“…SOD. 38 GSH is one of the key protectors of the hepatocytes and its homeostasis is associated with various toxin-induced liver injuries. GSH plays an important role against CCl 4 -induced injury by covalently binding to CCl 3…”
Section: Discussionmentioning
confidence: 99%
“…The free-radical scavenging potential and the inter-linked antioxidant components in the plant extract reportedly played a critical role in hepatotoxicity which was mediated by the actions of free-radicals on hepatocytes leading to cell necrosis [ 81 ]. In this connection, the Suaeda vermiculata aq.-ethanolic extract also showed free-radical inhibition properties, and the data reported in this study is following previously published reports demonstrating the hepatoprotective effects in CCl 4 -induced extensive liver damage models by the aq.-ethanolic extract containing antioxidant compounds as part of the mother liquor obtained from the plant [ 56 , 57 , 58 , 66 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, there was a surge in serum level of ALT, AST and ALP following exposure to rifampicin and CCl 4 . This indicated toxicant-induced hepatocellular damage [45]. Studies have shown that rifampicin-induced hepatotoxicity and nephrotoxicity involves the activation of pregnane X receptor (PXR).…”
Section: Discussionmentioning
confidence: 99%